Is more better? An immune-based approach to anti-HPV vaccine efficacy - Pawliczak, Rafał (Menopause Review/Przegląd Menopauzalny, 2010)
Summary Natural history studies conducted over the past 20 years have demonstrated that human papillomavirus (HPV) infection is a necessary prerequisite for the development of cervical cancer, the second most frequent cause of death in young women. Recently, two anti-HPV vaccines have been approved for immunoprophylaxis of cervical cancer: a quadrivalent vaccine containing L1 virus-like particles (VLPs) of HPV types 6, 11, 16 and 18, and a bivalent vaccine containing VLPs of types 16 and 18. In efficacy trials involving young women, both vaccines produced outstanding efficacy against primary and secondary endpoints associated with the vaccine type HPVs and were highly and consistently immunogenic. This review is focused on comparing safety and efficacy of both available vaccines.